Entrenchment, embeddedness, and entanglement: A dynamic complexity view - Herdina, Philip (Entrenchment and the psychology of language learning: How we reorganize and adapt linguistic knowledge, 2017)
The authors approach entrenchment from the perspective of dynamic complexity theory. Complex dynamic systems properties are emergent and result from the incremental effect of frequencies of occurrence. The mode of occurrence is contextualized: Effects of frequency contain traces of previous occurrences. So the distribution patterns of language units are not equiprobable, and context of use must not be ignored. Language is not a homogeneous system but consists of at least three identifiable and interacting subsystems—the ideal type representation of language, learner systems, and speaker systems—in which differing effects of frequency of occurrence of a language unit will be observed in the respective language system. Language units can show a degree of variation (drift) without resulting systemic effects (shift). When investigating frequency effects, we have to distinguish between effects on the unit and effects on the system, as these cannot be coextensive. In order to be able to specify the effects of frequency, we have to be able to determine the initial state of the affected system. The initial state is specified by a process called anchoring. Because the frequency effect is nonlinear, entrenchment can be a result of both high-frequency associations, and therefore a high degree of embeddedness, or low-frequency associations, resulting in a low degree of embeddedness or type or token isolation. Language units are subject not merely to systematic associations (embedding) but also to idiosyncratic and unsystematic associations. The principle of entanglement identifies the possibility of cross-categorical and cross-linguistic associations. The definition of entrenchment in a dynamic system is based on stability rather than invariability. Stability can be achieved by a process of adaptation to the language environment (lexicalization or regularization). Language memory is dynamic and interactive and results from interaction between individual memory and collective memory. Language retention is autopoietic and pragmatic as frequency of use results in retention and retention results in frequency of use. Linguistic memory is therefore not restricted to the individual language user. The variable effect of frequency is to be attributed to the fact that the frequency effect is a complex function (containing more than one interacting variable) and not a unit property. The interacting and interdependent variables have a dynamic effect. Explanations of frequency effects and language change have to complement efficient cause explanations by final cause explanations using attractors and attractor states to identify converging patterns. (PsycInfo Database Record (c) 2025 APA, all rights reserved) (Source: create)